PEMBAHARUAAN HUKUM SISTEM PERADILAN PIDANA DALAM RUU KUHAP - Indra Ariska, Dudung (Yustitia, 2019)
More than thirty years of the Penal Procedure Code are implemented in Indonesia. Law No. 8 of 1981 concerning the criminal procedural law in the beginning was seen as a "great work" of the Indonesian people for respecting human rights in general, and especially for those involved in criminal cases. However, now the Penal Procedure Code is deemed no longer in line with "changes in the constitutional system and legal developments in the community so that it needs to be replaced with a new penal procedural law" (consideration of " the letter c" of the Penal Procedure Code). In the general explanation of the Penal Procedure Code (KUHAP), a number of indicators were put forward which showed that the Penal Procedure Code was outdated